A review of recent advancement in laboratory diagnostic testing for neurodegenerative diseases - Abdullah Mohammed Fahad AlDowairej , Thamer Nasser Mohammed Alshahrani , Ahmad Abdulaziz Mohammed Albahlal , Abdullah Mohammed Abdulaziz Alsubaie , Saeed Abdullah Saeed Badogish , Abdulhadi Ali Homidi Alanazi; Abdullah Lafi Nwar Almutairi , Mazyad Eid Qarash Alotabi , Naif fahad Nasser Almusabbihi , Abdullatif Dakhilallah Rajaallah Alharthi , Zayed Mohammed Almohammed; Amnah Ali Mohammed Mobarki , Fahad Faleh Alresheedi , Khalid Mohammed Alzoughaibi , Ahmed Mohammed Mousa Ayyashi (Journal of International Crisis and Risk Communication Research, 2024)
Neurodegenerative diseases (NDDs), such as Alzheimer's disease (AD), Parkinson's disease (PD), and prion diseases, are characterized by the accumulation of misfolded proteins and are projected to become the second leading cause of death worldwide by 2040. The development of sensitive and efficient detection technologies for these disorders is crucial for early diagnosis and understanding the underlying pathological mechanisms. This review critically evaluates recent progress in the use of electrochemical and optical biosensors for the detection of NDDs. Optical biosensors, such as surface plasmon resonance imaging (SPRi), have been employed to detect AD biomarkers, including amyloid-β (Aβ), tau, and apolipoprotein E (ApoE), with high sensitivity. Similarly, quantum dot (QD)-based biosensors have been developed for detecting PD biomarkers, such as mitochondrial complex I abnormalities and dopamine levels. Electrochemical biosensors have also been utilized for the detection of AD and PD biomarkers, employing various strategies such as the use of specific antibodies, aptamers, and nanomaterials. For prion diseases, both optical and electrochemical biosensors have been developed, utilizing techniques such as SPR, chemiluminescence, and field-effect transistors (FETs). Despite these advancements, challenges remain in integrating multiple analytical technologies onto a single platform, transitioning from the development phase to commercialization, and exploring new nanomaterials and biomimetic surfaces to further enhance the sensitivity and reliability of NDD detection. Addressing these challenges will be essential for the continued evolution of biosensors and their translation into point-of-care diagnostic tools for NDDs.